2021
DOI: 10.47836/pjtas.44.2.02
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Endophytic Actinomycetes Producing Indole-3- Acetic Acid and In vitro Evaluation of Plant Growth-promoting Activity on Brassica oleracea L.

Abstract: The evaluation of endophytic actinomycetes diversity, growth-promoting strain effects on cauliflower seeds germination, and in vitro organogenesis are the objectives in this study. Moreover, 15 strains from 125 isolates were determined to produce indole-3- acetic acid (IAA), where majority was obtained from roots (66.67%), followed by from branches (26.67%) and leaves (6.67%). Specifically, Jatropha sp. is a plant species with the most endophytic actinomycetes content compared to others. In addition, all endop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
1
0
0
Order By: Relevance
“…It is a signaling molecule involved in cell division and root extension (Vurukonda et al, 2021). Moreover, several studies have reported the capacity of rhizospheric Streptomyces to synthesize IAA and other indolic derivates in liquid media (Khenaka et al, 2019;Oleńska et al, 2020;Ali et al, 2021). In our investigation, all isolates demonstrate the ability to produce IAA in medium amended with L-Trp, which is certainly synthesized via L-Trp-dependent pathway.…”
Section: In Vivo Bioassay Against S Scabies On Radish Seedlingsupporting
confidence: 50%
“…It is a signaling molecule involved in cell division and root extension (Vurukonda et al, 2021). Moreover, several studies have reported the capacity of rhizospheric Streptomyces to synthesize IAA and other indolic derivates in liquid media (Khenaka et al, 2019;Oleńska et al, 2020;Ali et al, 2021). In our investigation, all isolates demonstrate the ability to produce IAA in medium amended with L-Trp, which is certainly synthesized via L-Trp-dependent pathway.…”
Section: In Vivo Bioassay Against S Scabies On Radish Seedlingsupporting
confidence: 50%